2017
DOI: 10.7554/elife.29285
|View full text |Cite
|
Sign up to set email alerts
|

Gyrification of the cerebral cortex requires FGF signaling in the mammalian brain

Abstract: Although it has been believed that the evolution of cortical folds was a milestone, allowing for an increase in the number of neurons in the cerebral cortex, the mechanisms underlying the formation of cortical folds are largely unknown. Here we show regional differences in the expression of fibroblast growth factor receptors (FGFRs) in the developing cerebral cortex of ferrets even before cortical folds are formed. By taking the advantage of our in utero electroporation technique for ferrets, we found that cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…The cortical folding has been hypothesized to be a result of the regional neuronal differentiation and migration (Zilles, Armstrong, Schleicher, & Kretschmann, ), and mechanical tension by the underlying axonal connections (Van Essen, ). More recent research revealed that an increased number of neural progenitors in the subventricular zone are essential for gyrification of the cortical cortex (Matsumoto, Shinmyo, Ichikawa, & Kawasaki, ). The GI is an index representing the degree of gyrification; the ratio of the contour of the pial surface against the outer contour of the cerebral cortex, representing the degree of cortical folding (Matsuda & Ohi, ).…”
Section: Discussionmentioning
confidence: 99%
“…The cortical folding has been hypothesized to be a result of the regional neuronal differentiation and migration (Zilles, Armstrong, Schleicher, & Kretschmann, ), and mechanical tension by the underlying axonal connections (Van Essen, ). More recent research revealed that an increased number of neural progenitors in the subventricular zone are essential for gyrification of the cortical cortex (Matsumoto, Shinmyo, Ichikawa, & Kawasaki, ). The GI is an index representing the degree of gyrification; the ratio of the contour of the pial surface against the outer contour of the cerebral cortex, representing the degree of cortical folding (Matsuda & Ohi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Combination of in situ hybridization and immunostaining was described previously (Matsumoto et al, 2017). Briefly, after hybridization, sections were incubated with mouse anti-Pax6 antibody (Abcam; RRID:AB_1566562) and rabbit anti-Tbr2 antibody (Abcam; RRID: AB_778267).…”
Section: Figurementioning
confidence: 99%
“…RNA probes for mouse Fgfr1, Fgfr2, and Fgfr3 were described previously (Matsumoto et al, 2017). To make RNA probes for mouse Etv5 and Spry2, cDNA fragments were amplified with RT-PCR using the following primers.…”
Section: Figurementioning
confidence: 99%
“…The differential growth across the cortex, the migration of neurons along radial glia, and/or the differential expansion of upper versus lower layer neurons are a few proposed mechanisms generating variation in cortical folding between species (Richman et al, 1975;Van Essen, 1997;Toro and Burnod, 2005;Xu et al, 2010;Chen et al, 2013;Striedter et al, 2015;Fernández et al, 2016;Tallinen et al, 2016;Razavi et al, 2017). Modifications to neurogenetic programs are well-documented sources of variation across species, and experimental manipulations of cell proliferation during development impact cortical composition, as well as cortical folding (Dyer et al, 2009;Clowry et al, 2010;Striedter, 2008, 2011;Charvet et al, 2017ab;Lewitus et al, 2013;McGowan et al, 2012McGowan et al, , 2013Nonaka-Kinoshita et al, 2013;Borrell and Götz, 2014;Otani et al, 2016;Tallinen et al, 2016;Toda et al, 2016;Matsumoto et al, 2017;Shinmyo et al, 2017;de Juan Romero and Borrell, 2017). We suggest that the differential composition of neurons across the depth of the cortex may cause major differences in white matter tension between species.…”
Section: Cortico-cortical Projections and Gyrificationmentioning
confidence: 99%